Edukasi Gizi Pencegahan Anemia pada Santriwati Sekolah Islam Pondok Pesantren Minhajushshoobiriin Tingkat Ulya Kecamatan Ciracas - Megah Stefani; Syawalna Azizah; Amalia Sholeha; Ria Agustin; Mariyah Ulfa; Dwi Cahayani (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The prevalence of anemia in adolescent girls is 48.9%, which means that 3-4 out of 10 adolescent girls in Indonesia suffer from anemia. The purpose of this nutrition education program is to educate adolescent girls about the importance of consuming foods rich in iron minerals as an effort to prevent anemia by using learning media in the form of animated videos and lecture methods. The implementation location is at the Minhajushshoobiriin Islamic Boarding School, Cibubur, East Jakarta. The target of this education is 20 respondents of female santri of the Minhajushshoobiriin Islamic Boarding School at the ulya level, aged between 15-18 years. The results of the statistical difference test showed that there was a significant difference with a p-value = 0.001 (<0.05) between the scores of the knowledge questionnaire before and after the program, indicating that there was a significant effect between the provision of nutrition education through the PASTI CERIA program conducted on the knowledge of adolescent girls about anemia.